Maternal and Infant Mortality Rates’s Contributing Factors Description and Its Prevention in Kencong Healthcare Center, Jember Regency : A Descriptive Study - Parti, Dita Diana; Firdaus, Jauhar; Sakinah, Elly Nurus; Lubis, Arinie Awindya; Pattipeilohy, Florence Marianty (UNUSA Press, 2024)
Background: Maternal Mortality Rates (MMR) and Infant Mortality Rates (IMR) are two of the indicators on the success of health programs in Indonesia. Jember has become the district with the highest rate of maternal and infant deaths throughout 2020-2021. Methods: This research assessed the contributing factors of MMR and IMR in Puskesmas Kencong, Jember Regency. This study uses a qualitative descriptive research design. Data in this study were taken by conducting interviews to fill out questionnaires to mothers who had given birth at least once and the Coordinating Midwife and Head Midwife of PONED (Basic Emergency Neonatal Obstetrics Services) at the Puskesmas Kencong. Then the data from the questionnaires and interviews will be processed and then explained in the narrative. Results:. Based on data from questionnaires filled out by 37 respondents, as well as questions posed to the midwife, Puskesmas Kencong has fulfilled the requirements needed as a PONED Health Center according to PONED Guidelines. Conclusion: The PONED Health Center at Kencong Health Center has a low prevalence of MMR and IMR.